2017
DOI: 10.1053/j.seminhematol.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte generation and population homeostasis throughout life

Abstract: Immune aging is a multi-faceted process that manifests as reduced competence to fight infections and malignant cells as well as diminished tissue repair, unprovoked inflammation and increased autoreactivity. The aging adaptive immune system, with its high complexity in functional cell subpopulations and diversity of B and T cell receptors, has to cope with the challenge of maintaining homeostasis while responding to exogenous stimuli and compensating for reduced generative capacity. With thymic involution, naï… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 37 publications
0
57
1
2
Order By: Relevance
“…In old mice, we have previously shown that B‐cell depletion reactivates B lymphopoiesis in the BM (Keren et al, ). However, reconstitution may also be derived from homeostatic proliferation of residual B cells in the periphery (Yanes, Gustafson, Weyand, & Goronzy, ). While generation in the BM gives rise to a new, diverse young‐like B‐cell population, homeostatic proliferation leads to expansion of residual selected clones and oligomonoclonality (Yanes et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In old mice, we have previously shown that B‐cell depletion reactivates B lymphopoiesis in the BM (Keren et al, ). However, reconstitution may also be derived from homeostatic proliferation of residual B cells in the periphery (Yanes, Gustafson, Weyand, & Goronzy, ). While generation in the BM gives rise to a new, diverse young‐like B‐cell population, homeostatic proliferation leads to expansion of residual selected clones and oligomonoclonality (Yanes et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, reconstitution may also be derived from homeostatic proliferation of residual B cells in the periphery (Yanes, Gustafson, Weyand, & Goronzy, ). While generation in the BM gives rise to a new, diverse young‐like B‐cell population, homeostatic proliferation leads to expansion of residual selected clones and oligomonoclonality (Yanes et al, ). To study the reconstituted peripheral B‐cell compartment in old mice, we have first determined their regenerative source.…”
Section: Resultsmentioning
confidence: 99%
“…Our data on TF networks in naïve CD4 T cells are consistent with the concept that immune aging involves the activation of T‐cell differentiation pathways resulting in a loss of naivety and stemness (Goronzy et al, ). Throughout adult life, the T‐cell compartment is maintained by homeostatic proliferation that is under the control of cytokines as well as requires survival signals from TCR (Goronzy & Weyand, ; Yanes, Gustafson, Weyand, & Goronzy, ). Cytokine‐driven differentiation is a hallmark of virtual memory CD8 cells that accumulate in the mouse with age (Nikolich‐Zugich, ).…”
Section: Discussionmentioning
confidence: 99%
“…In short, the cells of the lung and their inter-communication that is necessary for coordinated immune responses become dysregulated with advancing age (50). In addition, multiple changes in the adaptive immune system associate with aging and reflect a growing state of immunosenescence with diminished efficacy of responses to diverse microbial challenges (166,322,557), which may further contribute to the increased susceptibility to pneumonia among the elderly. Modification of compromised immunity resulting from the chronic inflammation and/or immunosenescence of aging may represent targets of future pneumonia risk reduction, once better defined.…”
Section: A Agementioning
confidence: 99%